Raptors: Diurnal and Nocturnal Birds of Prey (DigitalCommons@University of Nebraska - Lincoln, 2002)
What is a Raptor? A raptor is a bird of prey that is known for its predatory habits of feeding on other animals. This group of birds possesses several unique anatomical characteristics that allow them to be superior hunters. These include excellent sensory abilities such as binocular vision and keen hearing in order to detect prey, large powerful grasping feet with razor-sharp talons for catching prey, and generally large, hooked bills that can tear prey. There are 30 species of hawks, falcons, and eagles, as well as 18 species of owls breeding in North America. In this large group of birds, there are diurnal, or daytime, species such as hawks, falcons, and eagles, and nocturnal, or nighttime, species, such as owls. The Barn Owl is the preeminent nighttime hunter. with its facial disk and asymmetric ears, it has a keen sense of hearing which allows it to detect and capture prey in complete darkness. Should We Be Concerned About the Conservation Status of Raptors? Yes. Throughout the 20th century, raptors were impacted greatly by human disturbances such as habitat loss, shooting and environmental contaminants. Many raptor species such as the Bald Eagle and Peregrine Falcon sharply declined as a direct result of the use of the pesticide DDT. However, their numbers have rebounded since DDT use was restricted in the 1970s. The Peregrine Falcon was recently removed from the list of Endangered and Threatened Species in the U.S. (25 Aug 1999), and the Bald Eagle was recently proposed for delisting (6 July 1999) due to its increase from 417 pairs in 1963 to 6,334 pairs in 2000. Many long-distance migrants, such as Swainson’s and Broad-winged hawks, have experienced declines due to habitat destruction and hazards such as pesticide use in their wintering grounds. Swainson’s hawks breed in the western and Midwestern U.S. and Canada and migrate all the way to central Argentina for the winter. Conditions on the migratory route as well as in the wintering countries have had a major impact on their populations returning to ...